A novel freeze corer for characterization of methane bubbles and assessment of coring disturbances. (1st April 2019) - Dück, Yannick; Liu, Liu; Lorke, Andreas; Ostrovsky, Ilia; Katsman, Regina; Jokiel, Christian
Abstract: Aquatic ecosystems with organic‐rich sediments are a globally significant source of methane to the atmosphere. In shallow waters, ebullition is often a dominant emission pathway of methane. Current knowledge on the processes controlling gas bubble formation and persistence in aquatic sediments is limited. An important prerequisite for accurate quantification of the structure and methane bubbles in sediment samples is to preserve the ambient in situ conditions during the withdrawal process and further analysis. A novel freeze corer has been developed that facilitates sampling of gas‐bearing soft sediments for X‐ray computer tomography. The sampler allows freezing sediment inside a double‐walled corer with a mixture of dry ice and ethanol. This corer has moderate costs and offers important advantages for gassy sediment sampling. Its simplicity and robustness allow to perform sampling from a small boat and the ability to characterize in situ sediment features. The applicability of this freeze coring technique for gas bubble quantification was validated during laboratory experiments aimed to investigate the effects of freezing on sediment gas content, bubble size distribution, and their geometry by comparing computer tomography scans of unfrozen vs. frozen cores. The performance of the corer was further evaluated during field conditions in Lake Kinneret (the Sea of Galilee, Israel). The results demonstrate the suitability of the freeze‐coring method for in situ preservation of gas‐bearing sediments. The sediment structure, however, showed some displacements of sediments layers and bubble abundance in some core regions. Future investigations are needed to address the nature of disturbances of the frozen sediment.